Pengaruh Word of Mouth, Kualitas Layanan, Atmosphere, Kualitas Produk, Lokasi, dan Brand Equity Terhadap Keputusan Pembelian Pada D’Kovi Turen. (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACTPhenomena that occur at this time word of mouth, service quality, atmosphere, product quality, location, and brand equity become the main topics in the marketing world because they are able to make a major contribution to sales, so as to improve purchasing decisions.This research was conducted in D'Kovi, Turen sub-district of Malang, with the aim to analyze the effect of word of mouth, service quality, atmosphere, product quality, location, and brand equity on purchasing decisions partially or simultaneously, the variables used were word of mouth, service quality, atmosphere, product quality, location, and brand equity as independent variables, while purchasing decisions as the dependent variable. The sample used was visitors to D'Kovi, Turen sub-district, Malang district with 94 respondents using a survey method. The method used is a questionnaire. The analytical tool used is test instrument, classic assumption test, normality test, multiple linear regression test, hypothesis test and coefficient of determination test with the help of SPSS 20.0 software.The results showed that Word of Mouth (X1), Service Quality (X2), Atmosphere (X3), Product Quality (X4), Location (X5), and Brand Equity (X6) had a joint (simultaneous) effect on Purchasing Decisions (Y) in D'Kovi, Turen sub-district, Malang district. Keywords: word of mouth, service quality, atmosphere, product quality, location, brand equity and purchasing decisions